Synthesis and characterization of the first phosphonic diamide containing thiazolyl groups: Structural properties and tautomeric equilibrium - Gholivand, Khodayar (2010)
A new phosphonic diamide containing thiazolyl rings, N,N0 bis(2-thiazolyl) phenylphosphonic diamide, with general formula H5C6P(O)[NHCN(CH)2S]2 (1), was synthesized and characterized by NMR, IR, UV, EI mass-spectrometry and elemental analysis. The X-ray diffraction structure obtained for 1 shows that the crystalline compound exists in the imine form, forming centro-symmetric dimers which are produced by intermolecular cooperative hydrogen bonds leading to a two-dimensional polymeric chain. The preferred tautomeric and conformational equilibria have also been identified in solution. Thus, a tautomeric equilibrium of 97:3% between the amine:imine form is observed in DMSO-d6. Structural and conformational properties are analyzed using a combined approach involving crystallographic data, vibrational spectra and theoretical calculations at the B3LYP and MP2 (with 6-311++G and CBSB7 basis sets) level of approximations.